Stress and its effect on medical students Performance in Tikrit University College of Medicine - Essa, Athraa (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Medical education is perceived as being stressful, & a high level of stress may have a negative effect on cognitive functioning & learning of students in a medical school. Objectives: To determine the prevalence of perceived stress among medical students & to observe an association between the levels of stress & their academic performance, including the sources of their stress & their coping strategies. Methodology: This cross-sectional study was conducted on one hundred eighty medical students from first stage to sixth stage from the Tikrit were enrolled in the study. The study was conducted using Kessler10 psychological distress inventory, which measures the level of stress according to none, mild, moderate, & severe categories. The prevalence of stress was measured & compared with the six study variables, such as gender, living accommodation, academic year, regularity to course attendance, academic grades, & perceived physical problems Result: The response rate among the study subjects was 100% (n=180). The total prevalence of stress was 57.2%, & the prevalence of severe stress was 12.8%. The prevalence of stress was higher among females (69.9%) than among males(42.9%). 2=16.34, p<0.001). The prevalence of stress was higher in students living at dormitory (31.6%) than students live at parental home (25.5%) but the severity of stress was higher in those students. The prevalence of stress was higher during the preclinical group mostly in third year students (76.7%) & in students who attend irregularly (73.9%). Exams (73%) & load of study (49.5%) are the most powerful stressors. Spend time with friends, sleeping, prayer, music, going into isolation or sports are various coping mechanisms. The academic performance was decline with increase stress level. Physical problems are associated with high stress levels. Conclusion: The prevalence of perceived stress seems to be high among medical students & in all level was higher in female than male. Preclinical group of students had more stress than clinical group & most of students who attend irregularly had high level of stress, which tends to affect not only their academic performances but also all aspects of health. Recommendation: Review of academics & exam schedules, more leisure time activities, better interaction with the faculty & proper guidance, advisory services & peer counseling at the campus could do a lot to reduce the stress.